2021
DOI: 10.1182/blood.2020008501
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand disease: what does the future hold?

Abstract: Von Willebrand disease (VWD) is characterized by its heterogeneous clinical manifestation, which complicates its diagnosis and management. The clinical management of VWD has remained essentially unchanged over the last 30 years or so, using von Willebrand factor (VWF) concentrates, desmopressin and anti-fibrinolytic agents as main tools to control bleeding. This is in contrast to hemophilia A, for which a continuous innovative path has led to novel treatment modalities. Despite current VWD management being con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 82 publications
0
26
0
1
Order By: Relevance
“…Careful review of literature revealed a delicate study on the type 2A VWD associated VWF-437-442 mutant 43 . This mutant has lost the ability to form multimers and has defects in regulated storage, but co-expressed normal D1D2 completely restored multimerization of the mutant 43 Despite current clinical management of VWD being considered effective with limited innovation in terms of treatment over last 30 years, quality-of-life studies consistently reveal a higher than anticipated burden of VWD on patients, which is particularly true for women 5 . As the VWD is an ideal target for gene therapy where a single treatment could potentially result in long term correction of the disease and even partial correction could have benefits in lowering the bleeding risks, like in the case of hemophilia 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful review of literature revealed a delicate study on the type 2A VWD associated VWF-437-442 mutant 43 . This mutant has lost the ability to form multimers and has defects in regulated storage, but co-expressed normal D1D2 completely restored multimerization of the mutant 43 Despite current clinical management of VWD being considered effective with limited innovation in terms of treatment over last 30 years, quality-of-life studies consistently reveal a higher than anticipated burden of VWD on patients, which is particularly true for women 5 . As the VWD is an ideal target for gene therapy where a single treatment could potentially result in long term correction of the disease and even partial correction could have benefits in lowering the bleeding risks, like in the case of hemophilia 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Its normal function requires the assembly of VWF into large disulfide-linked multimers [1][2][3] . Defects in VWF multimerization cause several forms of von Willebrand disease (VWD), the most common inherited bleeding disorder worldwide [4][5][6][7] .…”
mentioning
confidence: 99%
“…In this review, we described two options, which at the relative short term could become available for these patients. A more extensive description of the different opportunities for innovation was published in 2021 10 . These innovative paths are not only limited to protein‐based strategies but also genetic approaches are in early stage preclinical development.…”
Section: Discussionmentioning
confidence: 99%
“…A more extensive description of the different opportunities for innovation was published in 2021. 10 These innovative paths are not only limited to protein-based strategies but also genetic approaches are in early stage preclinical development. With genetic approaches, one should think of siRNA-based techniques to silence mutant alleles or even gene therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation